1992
DOI: 10.1111/j.1349-7006.1992.tb01960.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of the Combination of Antineoplaston A‐10 Injection with a Small Dose of cis‐Diamminedichloroplatinum on Cell and Tumor Growth of Human Hepatocellular Carcinoma

Abstract: The inhibitory effects of a combination of Antineoplaston A‐10 Injection with a small dose of m‐diamminedichloroplatinum (CDDP) on cell and tumor growth was tested in in vitro and in vivo settings. A human hepatocellular carcinoma cell line (KIM‐1) was used for the cell growth and transplanted tumor growth studies. In the cell growth study, one‐hour exposure of KIM‐1 cells to CDDP in the medium at concentrations of 0.5, 1.0, and 2.0 μg/ml inhibited cell growth dose‐dependently. Continuous exposure of cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Several glutarimide derivatives have been reported to possess significant anticancer activity. For example, PCNU [λ-(chloroethyl)-3-(2,6-piperidinedione)-1-nitrosourea] can easily cross the blood−brain barrier, and it shows activity against brain tumors; aminoglutethimide is a strong inhibitor of steroid biogenesis and is used in the treatment of metastatic breast cancer; and antineoplaston A10 ( N -phenylacetyl-α-aminoglutarimide), which has recently been introduced into experimental chemotherapy, has a remarkable anticancer activity, particularly against brain tumors, and it shows very low toxicity. , In vitro studies employing the thermal denaturation of DNA as well as fluorescence spectroscopy have revealed that antineoplaston A10 may bind weakly and noncovalently with DNA . Eriguchi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several glutarimide derivatives have been reported to possess significant anticancer activity. For example, PCNU [λ-(chloroethyl)-3-(2,6-piperidinedione)-1-nitrosourea] can easily cross the blood−brain barrier, and it shows activity against brain tumors; aminoglutethimide is a strong inhibitor of steroid biogenesis and is used in the treatment of metastatic breast cancer; and antineoplaston A10 ( N -phenylacetyl-α-aminoglutarimide), which has recently been introduced into experimental chemotherapy, has a remarkable anticancer activity, particularly against brain tumors, and it shows very low toxicity. , In vitro studies employing the thermal denaturation of DNA as well as fluorescence spectroscopy have revealed that antineoplaston A10 may bind weakly and noncovalently with DNA . Eriguchi et al .…”
Section: Introductionmentioning
confidence: 99%
“…16 Antineoplaston AS2-1 has shown a cell differentiation effect in many malignant cells such as human erythroleukemic cells (K562) 17 and human hepatocellular carcinoma cells (KIM-1). 18 These findings suggest the diverse effects of antineoplaston AS2-1 on the genes controlling cell differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…They found AS2-1 to induce cell differentiation, as shown by hemoglobin production in erythroleukemia cells. Tsuda et al (1992) demonstrated in an electron microscopic study that A-10 injection in combination with small doses of CDDP induces morphological differentiation in human hepatocellular carcinoma. Liau et al (1989) suggest that the hypomethylation of nucleic acids by AS2-1 may be essential for inducing cell differentiation.…”
Section: Discussionmentioning
confidence: 99%